A review of recent development in numerical simulation of ultrasonic-assisted gas-liquid mass transfer process - Tamidi, A.M. (Elsevier Ltd, 2021)
Ultrasonic Irradiation (UI) is one of the technologies used to enhance the gas-liquid mass transfer (GLMT) process. Sonophysical effects such as acoustic streaming, jet flow, acoustic fountain, and atomization are the main factors that enhance the mass transfer coefficient. Numerical simulation can provide insight into the complex fluid behaviors under the influence of ultrasound waves such as fluid flow, mixing, cavitation, and mechanism of GLMT. Study on numerical simulation related to high frequency ultrasound waves, particularly on the formation of acoustic fountain and atomization is found to be limited. Recently developed numerical studies of the ultrasonic-assisted GLMT process are reviewed especially on hydrodynamics and mass transfer modeling for varied frequencies of the ultrasound wave. Challenges and future directions on current modeling approaches are analyzed to highlight the potential of numerical modeling of ultrasonic-assisted GLMT phenomena for process design, scale-up, and optimization. Â© 2021 Elsevier Ltd